1992
DOI: 10.1121/1.403997
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic prototypes: Influence of place of articulation and speaking rate on the internal structure of voicing categories

Abstract: In this investigation, the effects of context on the perception of voicing contrasts specified by voice-onset-time (VOT) in syllable-initial stop consonants were examined. In an earlier paper [J.L. Miller and L.E. Volaitis, Percept. Psychophys. 46, 505-512 (1989)], it was reported that the listener's adjustment for one contextual variable, speaking rate, was not confined to the region of the phonetic category boundary, but extended throughout the phonetic category. The current investigation examines whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
205
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(233 citation statements)
references
References 0 publications
23
205
3
Order By: Relevance
“…There is evidence that the identity of a vowel is influenced by its duration and that the perceived duration of a vowel is affected by the rhythm of the preceding sound sequence (Ainsworth, 1974). For conso- nants, as speech is slowed, the phonetic category boundary for the contrast between initial voiced and voiceless stops moves toward longer VOT values (Summerfield, 1981), and the range of stimuli perceived as good exemplars of the category becomes wider (Miller & Volaitis, 1989;Volaitis & Miller, 1992). In our study, variations in the length of consonants and vowels that are due to natural rate modifications could affect processing of these segments and, consequently, syllable identification.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that the identity of a vowel is influenced by its duration and that the perceived duration of a vowel is affected by the rhythm of the preceding sound sequence (Ainsworth, 1974). For conso- nants, as speech is slowed, the phonetic category boundary for the contrast between initial voiced and voiceless stops moves toward longer VOT values (Summerfield, 1981), and the range of stimuli perceived as good exemplars of the category becomes wider (Miller & Volaitis, 1989;Volaitis & Miller, 1992). In our study, variations in the length of consonants and vowels that are due to natural rate modifications could affect processing of these segments and, consequently, syllable identification.…”
Section: Resultsmentioning
confidence: 99%
“…For song learning accuracy, there may be selection not only for the high level of learning precision observed in swamp sparrows [18] and other species, but also for the categorization and categorical perception of syllables and notes [43]. Research into categorization in speech has clearly shown that humans distinguish between more or less typical phonemes [4][5][6][7][8]. If similar psychological processes underlie preferences in swamp sparrows, this species might provide a model for understanding categorization in learned communication systems.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that humans can perceive the degree to which utterances are typical or 'good' exemplars of speech categories [4][5][6][7]. It is still debated exactly how this feat is accomplished: one possible mechanism is by learning 'prototypes', single summary representations of categories stored in long-term memory, while an alternative is by memorization of a large number of individual exemplars [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is also the case that stimuli which are unequivocal in their phonetic category membership may also be poorer members of a phonetic category. Volaitis and Miller showed that voiceless tokens with very long VOTs of 165 msec and greater were judged as poorer phonetic category members than those with shorter VOTs (Miller & Volaitis, 1989;Volaitis & Miller, 1992). Kessinger and Blumstein (manuscript) also showed that stimuli beginning with voiceless stops whose VOT was increased by 4/3 (mean VOT=180 msec, range: 136-225 msec) were rated as poorer exemplars than either unaltered stimuli or those that were increased by 2/3 (mean VOT=129 msec, range: 103-154 msec).…”
Section: Internal Structure Of Voiceless and Voiced Stop Categoriesmentioning
confidence: 99%